2010
DOI: 10.2319/092409-530.1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of surgically assisted rapid maxillary expansion and orthopedic maxillary expansion after 3 years' follow-up

Abstract: Objective: To evaluate the stability of surgically assisted rapid palatal expansion (SARME) and orthopedic maxillary expansion (OME) after 3 years of follow-up, and compare these changes with a control group. Materials and Methods: The subjects of the study were divided into three groups. Group 1 was composed of 10 patients (6 males, 4 females) with a mean age of 15.51 years (range: 13.33-17.58 years) and treated with OME, Group 2 comprised 10 patients (7 males, 3 females) with a mean age of 19.01 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
1
37
0
1
Order By: Relevance
“…The preoperative status in Part I was compared with the postoperative status in Part II. In addition, a previous, 3-year follow-up of both OME and SARME showed that the treatments remained stable in the patients when compared with a control group [33]. Hence, studies using a 6-month retention period, as in the present study, may report less relapse compared with those that use a 3-month stabilization period [34].…”
Section: Discussionsupporting
confidence: 48%
“…The preoperative status in Part I was compared with the postoperative status in Part II. In addition, a previous, 3-year follow-up of both OME and SARME showed that the treatments remained stable in the patients when compared with a control group [33]. Hence, studies using a 6-month retention period, as in the present study, may report less relapse compared with those that use a 3-month stabilization period [34].…”
Section: Discussionsupporting
confidence: 48%
“…When SARME is done first, the transverse correction precedes orthognathic surgery or the transverse deficiency is the only deformity 18 . According to many authors, it is a simple, stable and safe method of treatment 4,[19][20][21] . Skeletal changes and stability of dentofacial deformity correction using 2-D methods are well described in the literature [22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is multifactorial including genetic predisposition, developmental issues (e.g. : premature loss of teeth, parafunctional habits), asymmetric jaw, traumatic injuries and iatrogenic outcomes 2,4 . There is a transversal discrepancy between the maxillary and mandibular arch widths 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control group consisted of untreated, skeletal Class 1 subjects matched to the OME group in order to assess the effects of normal skeletal growth. The study showed that both the OME and the SARME procedures remained stable after three years with some amount of post retention relapses compared with the control group (Kurt et al 2010). In our clinic, we went one step further using a device with both tooth and bone anchorages (Fig.…”
Section: Surgically Assisted Rapid Maxillary Expansion (Sarme)mentioning
confidence: 99%